Sharp Turán inequalities via very hyperbolic polynomials - Dimitrov, Dimitar K. [UNESP]; Kostov, Vladimir P. (Elsevier, 2011)
We present new sharp inequalities for the Maclaurin coefficients of an entire function from the Laguerre-Pólya class. They are obtained by a new technique involving the so-called very hyperbolic polynomials. The results may be considered as extensions of the classical Turán inequalities. © 2010 Elsevier Inc.
Keywords: Hyperbolic polynomials; Laguerre-Pólya class; Maclaurin coefficients; Turán inequalities; Very hyperbolic polynomials